Promoting Open Education Resources – Blended Learning - Jadhav, Vaishali; Mahajan, Natasha (Innovational: Journal of Nursing and Healthcare, 2024)
The open educational resources (OERs) movement has empowered researchers and educators to become more innovative in their teaching and learning, through the openness and flexibility. The use and adaptation of OER have been recommended as a very cost-effective investment in quality teaching-learning. In conventional teaching practices, teachers mostly spend time developing learning materials, reviewing lecture notes, anticipating questions and formulating answers, and preparing for examinations. OERs are teaching and learning materials which are freely available and openly licensed. This method is no longer appropriate with learners current association with the technology. This research aims on promoting OER-based learning for undergraduate learners. Action research has been conducted to identify the learners adaptation to the new culture of OER-based blended learning. The learner performance records were also evaluated as a measure of quality of learning. The study has focused on how the OER material to be incorporated in the online course development in undergraduate learning. At the same time, researcher provides feedback on the use of OER-based learning methods. The study further elaborates on effective assessment activities which need to be used in OER-based learning. Learners were quite positive on these effective assessment activities. All over the studies specify the importance of incorporating OER in undergraduate online learning.